Challenging energy transition and green jobs: climate policy obstruction across borders - Dieter Plehwe; Jose A. Moreno; Moritz Neujeffski (Critical Policy Studies, 2025)
Critical policy mobility literature still does not usually account for transnational opposition dedicated to push back against policy transfer. To address this gap, we examine the case of policy instruments and discourses in support of energy transition and green jobs. In the 2000s, countries such as Spain, Germany, and Denmark adopted policies to fund renewable energy expansion. The success of feed-in-tariff and other policies served as an example for the promotion of public renewable energy investment in the US. Yet by the early 2010s, Spain and Germany discarded feed-in tariffs and erected regulatory barriers against renewables. An opposing discourse coalition amplified policy controversies in North America and Europe. The Institute of Energy Research (IER) orchestrated such efforts in opposition to president Obama's renewable energy program. An IER-led campaign focused on the denial of job market claims related to renewable energy (`green jobs'). Pursuing a multi-site case study of opposition strategy mobility, we examine the organizational and discursive building blocks of this campaign. The campaign against renewable policy and green jobs undermined popular renewable energy transition arguments in times of financial crisis in the United States, and was also mobilized against renewable programs in Canada and Europe.
Keywords: 330; Energy transition; green jobs; policy transfer; think tanks; opposition; strategy mobility